EFEK ANTIBAKTERI PASTA GIGI YANG MENGANDUNG TEA TREE OIL TERHADAP BAKTERIS. aureus, S. mutans dan S. viridans - Pudji Astuti; Zahara Meilawaty (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2013)
In the oral cavity there are a variety of microorganisms that live as normal flora of the oral cavity. The beneficial microorganisms and play a role in the development and defense of normal physiology in human . Components of these microorganisms can be pathogenic if the environment is compromised or are at a place that is not normal. Microflora commonly found in the oral cavity such as Staphylococcus aureus , Streptococcus mutans , and Streptococcus viridians . Today has developed various types of toothpaste containing various therapeutic materials to help improve oral health. The one that is being developed is much toothpaste containing tea tree oil, which has antibacterial and antiseptic properties are very high. The purpose of this study was to determine the antibacterial effect of toothpaste containing tea tree oil to the amount of bacterial growth of S. aureus , S. mutans and S. viridians . This study uses a sample of 1 piece of toothpaste containing tea tree oil and 1 non toothpaste tea tree oil as a control. Furthermore, the data obtained by analysis of Kruskal Wallis were tabulated and tested, then tested Man Whithney. The results showed the number of bacteria S. aureus , S. mutans and S.viridans on toothpaste containing tea tree oil, much less when compared with the number of bacteria in toothpaste that contains tea tree oil . The conclusion of this study is the toothpaste that contains tea tree oil has antibacterial effects against S. aureus, S.mutans and S.viridans.